Analysis Teacher and Student Perceptions of The Use Wordwall in Vocabulary Learning in The Eighth Grade of SMPN 1 Sitiung - Nanda, Dodi Widia; Lutfiah, Zumrotun; Prasetyaningrum, Galuh (TOFEDU: The Future of Education Journal, 2025)
This study aims to analyze the perception of teachers and students towards the use of Wordwall media in learning English vocabulary. Wordwall is one of the interactive digital learning media designed to make the learning process more interesting and fun. In this study, the author uses a qualitative research method with data collection techniques in the form of interviews with teachers and students of eighth grade of SMPN 1 Sitiung. The data was analyzed based on three main aspects, namely the effectiveness, benefits, and challenges in using Wordwall. The results of the study showed that teachers and students had a positive perception of the use of Wordwall. Wordwall is considered to be able to increase learning motivation, student involvement, and facilitate vocabulary understanding. However, there are also challenges such as limited internet access and technical constraints. This research also contributes to the development of technology-based learning strategies that are relevant and effective in the context of English learning at the junior high school level.